Acquired immunity against SARS‐CoV‐2 infection and vaccination - Laurent Renia; Lisa FP Ng (EMBO Molecular Medicine, 2023)
Abstract The ongoing severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pandemic has caused more than 700 million confirmed infections and ~7 million fatalities worldwide since its emergence in December 2019. SARS‐CoV‐2 is part of a family of positive‐sense, enveloped RNA viruses known as coronaviruses. Today, at least seven human coronaviruses have been identified and are known to cause respiratory tract illnesses with varying severity. The COVID‐19 pandemic spurred the generation of a vast amount of scientific knowledge on coronaviruses in record time, leading to a broad understanding of host immunity against SARS‐CoV‐2, and the rapid development of life‐saving vaccines (mainly mRNA and adenovirus‐ or inactivated virus‐based vaccines). Real world data on licensed SARS‐CoV‐2 vaccines have shown that efficacy ranges from 50 to 95% depending on viral variants, pre‐infections, and vaccine formulations, regimens, and combinations. While vaccination does markedly decrease the chances of infection and severe disease, breakthrough symptomatic and asymptomatic infections have occurred due to the emergence of immune escape virus variants. Therefore, despite these early successes, a better understanding of the mechanisms of protective immunity against infection is essential for the development of longer lasting and more efficient vaccines against SARS‐CoV‐2 and future coronaviruses.